The binary complex of poly(PEGMA-co-MAA) hydrogel and PLGA nanoparticles as a novel oral drug delivery system for ibuprofen delivery. Issue 16 (2nd November 2017) - Shang, Qing; Huang, Sijin; Zhang, Aixin; Feng, Jia; Yang, Song
Abstract: To improve the bioavailability of ibuprofen (IBU), we developed a novel binary complex of poly(PEGMA-co-MAA) hydrogel and IBU-loaded PLGA nanoparticles (IBU-PLGA NPs@hydrogels) as an oral intestinal targeting drug delivery system (OIDDS). The IBU-loaded PLGA NPs and pH-sensitive hydrogels were obtained via the solvent evaporation method and radical polymerization, respectively. The final OIDDS was obtained by immersing the hydrogel chips in the IBU-loaded PLGA NPs solutions (pH 7.4) for 3 d. The size distribution and morphology of cargo-free NPs were studied by laser granularity analyzer and transmission electron microscope (TEM). The inner structures of the pH-sensitive hydrogel chips were observed with an S-4800 scanning electron microscope (SEM). The distribution states of IBU in the OIDDS were also studied with X-ray diffraction (XRD) and differential scanning calorimetry (DSC). TEM photographs illustrated that the PLGA NPs had a round shape with an average diameter about 100 nm. Fourier transform infrared spectrum (FTIR) confirmed the synthesis of poly(PEGMA-co-MAA) hydrogel. The SEM picture showed that the final hydrogel had 3D net-work structures. Moreover, the poly(PEGMA-co-MAA) hydrogel showed an excellent pH-sensitivity. The XRD and DSC curves suggested that IBU distributed in the OIDDS with an amorphous state. The cumulated release profiles indicated that the final OIDDS could release IBU in alkaline environment (e.g. intestinal tract) at a sustained manner. Therefore, the novel OIDDS could improve the oral bioavailability of IBU, and had a potential application in drug delivery.